Oil spill simulation: A case study in the strait of Istanbul - Can, Sevilay; Celik, Fahri; Yilmaz, Huseyin; Bak, Osman Askin (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2007)
Safe ship operation in Turkish straits, the most important routes of oil transportation, is a fundamental issue. Turkish Straits connect the Black Sea and the Aegean Sea, and they enable direct transport of the oil produced in the northern Black Sea to Europe. There, about 15,000 tankers per year are going up continuously. This fact has inevitably increased the risk of catastrophic accidents and consequent oil spills, especially in the Istanbul strait. Large accidents occurring beside the mega city Istanbul (about thirteen millions of inhabitants) can be a great disaster directly attacking the life in this city. Therefore, in the event of an accident, efforts should be made to contain the spilled oil and minimize damage. This paper describes the numerical simulation of oil spill for two different points in Istanbul strait enabling us to estimate the effects in the case of a tanker accident. The output of the numerical simulation can be used to define and specify the proper methodology, and procedures for the Oil Spill Contingency Plan of Istanbul strait.
Keywords: oil spill; CFD; simulation; tanker accident; fluent; Istanbul; MODEL; BAY; Environmental Sciences & Ecology